Architectural Constraints for Pervasive Adaptive Applications - Straube, Christian; Schroeder, Andreas (Electronic Communications of the EASST, 2010)
To face the challenge in today's mobile applications, that software entities and devices enter and leave the application scope very frequently, component-based architectures are used more and more. With the flexibility of this concept and the ability to handle a huge amount of situations come inpredictability and less reliability of the application. This article presents a ``safety net'' weaved by architectural constraints and an internal DSL to ensure the integrity of the whole application even after multiple reconfigurations. With this integrated, not graph-oriented approach, software-systems can be much more flexible in combination with less code complexity, and the responsibility of architectural integrity is moved from the developer to the application.